Pengaruh Corporate Governance terhadap Kinerja Perusahaan dengan Pergantian Chief Executiv Officer Sebagai Variable Moderasi - Eci Siti Maesaroh; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research discusses the impact of corporate governance on company performance. The panel data used covered 105 companies listed on the Indonesian Stock Exchange (BEI) from 2021 to 2023. The results show that managerial ownership, institutional ownership and independent board of commissioners, members of audit committees, and exchange of CEOs have no significant influence on the company's performance.Management ownership has a positive impact on company performance, meaning that the higher the management ownership then the company performance will increase. Institutional owners also have a positive effect on corporate performance, because institutions can be an effective monitoring tool and reduce agency costs. Independent board of Commissioners has a good effect on the performance of the company, because the board can perform supervisory functions over corporate operations and reduce the likelihood of fraudulent financial reporting.The results of this study are consistent with the theory of agency, signaling theory, and agency theory that explains that corporate governance can improve corporate performance by reducing agency conflict and improving the efficiency of corporate resource management. The results also show that corporate governance plays an important role in improving company performance and can be an effective tool to increase company value.